Responses of signal crayfish Pacifastacus leniusculus to single short-term pulse exposure of pesticides at environmentally relevant concentrations - Malinovska, Viktoriia; Kuklina, Iryna; Lozek, Filip; Velisek, Josef; Kozak, Pavel (Environmental science and pollution research international, 2023)
Although pesticides are often discharged into surface waters in pulses as opposed to a sustained release, the effect of episodic pollution events on freshwater crayfish is largely unknown. We monitored change in heart rate and distance moved to assess the response of signal crayfish Pacifastacus leniusculus to short-term exposure to environmentally relevant concentrations of metazachlor (MTZ), terbuthylazine (TER), and thiacloprid (TCL). Crayfish exposed to 20 µg/L of MTZ exhibited a significant increase in mean heart rate and distance moved. Increased heart rate was detected at 118 ± 74 s post-exposure to MTZ. There were no significant differences in mean heart rate and distance moved in crayfish exposed to 6 µg/L of TCL and 4 µg/L of TER. A significant correlation between heart rate and distance moved was found in all exposed groups. These results suggest that pulse exposure to MTZ impact crayfish physiology and behavior during short-term period. With pulse exposure to TCL and TER, crayfish not exhibiting a locomotor response may continue to be exposed to lower, but potentially harmful, levels of pollutants. Evidence of the impacts of pesticide pulse at environmentally relevant concentrations on crayfish is scarce. Further study is required to determine the ecological effects of such events on freshwater crayfish.
Keywords: Water Pollutants, Chemical; Short-term exposure; Pesticides; Terbuthylazine; severní raci; Thiacloprid; Animals; Heart Rate; pesticidy; Astacoidea; srdeční frekvence; Locomotor activity Metazachlor; zvířata; Freshwater invertebrate; chemické látky znečišťující vodu